If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1d + 16 = 20 Reorder the terms: 16 + -1d = 20 Solving 16 + -1d = 20 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -1d = 20 + -16 Combine like terms: 16 + -16 = 0 0 + -1d = 20 + -16 -1d = 20 + -16 Combine like terms: 20 + -16 = 4 -1d = 4 Divide each side by '-1'. d = -4 Simplifying d = -4
| 13x^2-(10x^2+9)=0 | | -d+17=9 | | 24v=5v^2-5 | | 3u^2=-7u-2 | | 49b^2-9=0 | | (3x^2-15d)-(-10x^2-4d)=0 | | 4x^2-9x^2-36x-14= | | 2x-28=-58+7x | | 16c^2+40c+25=0 | | 2x-28=-28+7x | | 0.16c^2+0.40c+.25=0 | | -10w^7-(-14w^7-5n)=0 | | 5n-18=-18+n | | 9a^2-24a+16=0 | | -13.6+(-3.4c)+1.7c=3.4 | | (4s-2)(5s-4)= | | -3x^2+2x+12=0 | | 9d+4=4d+44 | | 7(x-6)=20.3 | | 2(a+4)=22.8 | | 11.6=2c-8 | | 6e-6=49.2 | | -d+15=11 | | 9(a+8)=135 | | 16x^2-16x-35=0 | | 1=2c-9 | | 8e-2=22 | | 16x^2-8x-8x+4=39 | | 3.4=-13.6+(-3.4c)+1.7 | | 0.20y-0.4=0.10y+2-0.5y | | 60x^2+34x-70=0 | | x(5x+2)=2x^2-2x+4 |